Comments on "Fertility as Consumption: Theories from the Behavioral Sciences" - Kiser, Clyde V.; Leibenstein, Harvey; Namboodiri, N. Krishnan; Scanzoni, John; Turchi, Boone A. (Journal of Consumer Research, 1979)
Clyde V. Kiser, Harvey Leibenstein, N. Krishnan Namboodiri, John Scanzoni, Boone A. Turchi; Comments on “Fertility as Consumption: Theories from the Behavi